Систематична та еколого-ценотична структура флори Тернопільського плато - Sobko, V.G.; Yavorivs'ky, R.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The leading families (10), 10 genera of flora and its 11 florocenotypes have been analyzed. It has been determined that it belongs to nemoral-steppe category of floras with petrophyton as its specific kernel. This flora is autochthonous with some migration elements.